CREATING A DIGITAL STORY OF BANTEN FOLKTALES FOR HIGHER EDUCATION STUDENTS - Yanti Anggraini; Rizky Wahyu Hadiyana (Journal of English Language Teaching and Literature (JELTL), 2019)
The aims of this study were: (1) to discover the target needs of higher education students, (2) to discover the learning needs of higher education students, and (3) to build-up a suitable digital story of Banten Folktales for higher education students. This was a Research and Development (R&D) study. The research procedure, adjusted from ADDIE model proposed by Taylor (2004), comprised of conducting the needs analysis, designing a course grid and a storyboard, developing the first draft of the digital story, evaluating the first draft, and producing the final draft. The instruments to collect the data were needs analysis questionnaire and correspondent survey questionnaires. The information from the needs analysis was analyzed quantitatively using frequency and rate, and after that the comes about were utilized as the premise to create the course grid and storyboard. The quantitative data from the correspondent survey was analyzed through descriptive statistics while the comments and suggestions were used to revise the first draft to be the final product of the digital story. The developed product was valid and appropriate after being evaluated in correspondent review phase in terms of its content and design with the average score 4.69 categorized as very highly valid.